FACTORS INFLUENCING STUDENTS’ GRAMMAR AND PRONUNCIATION ABILITY IN NUSA LONTAR HIGH SCHOOL (SMA NUSA LONTAR) - Richarda Nuryati Damut (JURNAL ILMIAH UNSTAR ROTE, 2025)
ABSTRACT This research, entitled Factors Influencing Students’ Grammar and Pronunciation Ability in Nusa Lontar Senior High School (SMA Nusa Lontar) aims to investigate the factors behind students’ low performance in grammar and pronunciation. The study focuses on identifying the reasons that contribute to these difficulties among Grade XI students. Using a qualitative descriptive approach and a case study design, data were collected through classroom observation, interviews, and documentation. The findings reveal that several factors influence the students’ low ability, including limited exposure to English, lack of practice, insufficient understanding of grammatical rules, lack of motivation in spending more time in studying English, and students’ low confidence in speaking. To face these challenges, the teacher develops some learning methods such as making more sentences to understand the contextual use of tenses, spending more time to learn about tenses, study how to pronounce words correctly and repeat the pronouncing, motivate the students more both in studying the grammar and pronunciation. From the results and discussion, the writer concludes that improving learning strategies, providing more speaking opportunities, and increasing students’ motivation can help enhance their grammar and pronunciation abilities. Key words: grammar, pronunciation, ability, English, students, senior high school